Natural dye sensitizer in dye sensitized solar cell - Nurain Najihah Alias,; Khatijah Aisha Yaacob, (Penerbit Universiti Kebangsaan Malaysia, 2016)
Blue-pea flower, turmeric, mulberries, brown rice, purple cabbage and Indian mulberry leave were successfully form on TiO2 mesoporous film using immersion method to produce TiO2 mesoporous photoanode for natural dye sensitized solar cells (DSSCs) assembly. The TiO2 mesoporous films were formed after calcinations at 450˚C for 30 min. The photoanodes were dipped in different types of natural dye for 24, 72 and 120 h. The properties of natural dye were investigated by ultraviolet-visible spectroscopy (UV-vis) and Fourier transform infrared spectroscopy (FTIR). From UV-Vis spectroscopy analysis, the wavelength range of the natural dye studied in this research lays between 350 and 800 nm. The FTIR result of the natural dye shows the present of intermolecular H-bond, C=O stretching vibration, C-O-C stretching vibration, C=C bending and C-H bending which was due to the component of anthocyanin, carotenoids and chlorophyll. The characterization including field emission scanning electron microscopy (FESEM), energy dispersive x-ray (EDX) and x-ray diffraction (XRD) were carried out on the TiO2 mesoporous film. On the other hand, the conductivity of electrolyte for liquid electrolyte, gel electrolyte and solid electrolyte were also investigated. Gel electrolyte has the highest conductivity, 26.1 mS/cm while liquid electrolyte and solid electrolyte obtained 17.34 and 0.45 mS/cm, respectively. Finally, solar cells were prepared by sandwiching the TiO2 mesoporous photoanode with Platinum (Pt) counter electrode. The results showed short circuit current, open circuit current voltage, fill factor and efficiency for all samples during the present of light. The highest efficiency was obtained from Blue-pea sample that immersed for 120 h with 0.123% efficiency.